Effects of mti-2 Transgenic Potato Plants on the Aphid Myzus persicae (Sternorrhyncha: Aphididae). (13th May 2010) - Saguez, Julien; Cherqui, Anas; Lehraiki, Salima; Vincent, Charles; Beaujean, Antony; Jouanin, Lise; Laberche, Jean-Claude; Giordanengo, Philippe
Abstract : Overexpressed in transgenic plants, protease inhibitors showed insecticidal effects against several insect taxa. We transformed potato internodes with the mustard trypsin inhibitor mti-2 gene. Among the 35 independent transgenic potato lines obtained via Agrobacterium tumefasciens transformation, four (DM6, DM7, DM11, and DM19) were selected for their high level of MTI-2 (at least to 30% of trypsin activity inhibition). Feeding assays were carried out to evaluate their effects on the green-peach aphid, Myzus persicae (Sternorrhyncha: Aphididae). Prereproductive period, nymphal mortality, adult fecundity, and doubling time of M. persicae populations were monitored on nontransformed potato plants (NT) and the four selected DM lines. Compared to NT plants, DM19 did not induce any effect on M. persicae . In contrast, DM7 and DM11 increased nymphal survival by approximately 20%. DM6 and DM11 lines slightly enhanced M. persicae daily fecundity and intrinsic rate of natural increase, leading to a reduction of the doubling time of the populations by 1 day. DM6 did not impact nymphal mortality, whereas with the DM11 almost all the nymphs survived. Potato plants transformed with the mti-2 gene variably affected the life history of M. persicae but did not show any insecticidal effect on the aphid.